The Influence of Principal Supervision, Work Discipline, and Work Motivation on Teacher Performance - Shafa' Muthi'ah; Aslamiah Aslamiah; Suhaimi Suhaimi (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
Teacher performance is a crucial factor in determining the quality of learning in elementary schools and is influenced by principal supervision, work discipline, and teachers’ work motivation. This study aimed to analyze the conditions of principal supervision, work discipline, work motivation, and teacher performance, as well as to examine the direct and indirect effects of principal supervision on teacher performance through work discipline and work motivation at public elementary schools in Teweh Tengah District. The study employed a quantitative approach involving all 105 teachers from eight public elementary schools in Teweh Tengah District using a total sampling technique. Data were analyzed descriptively using SPSS and inferentially using SmartPLS 4 through outer model and inner model testing. The findings indicated that all variables were categorized as high to very high. Inferential analysis showed that principal supervision, work discipline, and work motivation had positive and significant effects on teacher performance. The R-Square values demonstrated that the model explained 74.6% of the variance in teacher performance, 52.0% of the variance in work discipline, and 47.8% of the variance in work motivation. In addition, principal supervision had indirect effects on teacher performance through work discipline (3.1%) and work motivation (4.5%). These findings highlight the importance of sustainable academic supervision in improving teachers’ discipline, motivation, and performance.